Strategies for the prevention of perinatal hepatitis B transmission in a marginalized population on the Thailand-Myanmar border: a cost-effectiveness analysis - Devine, A; Harvey, R; Min, A; Gilder, M; Paw, M; Kang, J; Watts, I; Hanboonkunupakarn, B; Nosten, F; McGready, R (BioMed Central, 2017)
Background Data on the cost effectiveness of hepatitis B virus (HBV) screening and vaccination strategies for prevention of vertical transmission of HBV in resource limited settings is sparse. Methods A decision tree model of HBV prevention strategies utilised data from a cohort of 7071 pregnant women on the Thailand-Myanmar border using a provider perspective. All options included universal HBV vaccination for newborns in three strategies: (1) universal vaccination alone; (2) universal vaccination with screening of women during antenatal visits with rapid diagnostic test (RDT) plus HBV immune globulin (HBIG) administration to newborns of HBV surface antigen positive women; and (3) universal vaccination with screening of women during antenatal visits plus HBIG administration to newborns of women testing HBV e antigen positive by confirmatory test. At the time of the study, the HBIG after confirmatory test strategy was used. The costs in United States Dollars (US$), infections averted and incremental cost effectiveness ratios (ICERs) were calculated and sensitivity analyses were conducted. A willingness to pay threshold of US$1200 was used. Results The universal HBV vaccination was the least costly option at US$4.33 per woman attending the clinic. The HBIG after (RDT) strategy had an ICER of US$716.78 per infection averted. The HBIG after confirmatory test strategy was not cost-effective due to extended dominance. The one-way sensitivity analysis showed that while the transmission parameters and cost of HBIG had the biggest impact on outcomes, the HBIG after confirmatory test only became a cost-effective option when a low test cost was used or a high HBIG cost was used. The probabilistic sensitivity analysis showed that HBIG after RDT had an 87% likelihood of being cost-effective as compared to vaccination only at a willingness to pay threshold of US$1200. Conclusions HBIG following confirmatory test is not a cost-effective strategy for preventing vertical transmission of HBV in the Thailand-Myanmar border population. By switching to HBIG following rapid diagnostic test, perinatal infections will be reduced by nearly one third. This strategy may be applicable to similar settings for marginalized populations where the confirmatory test is not logistically possible.